1999
DOI: 10.1046/j.1460-9568.1999.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct populations of hypothalamic dopaminergic neurons exhibit differential responses to brain‐derived neurotrophic factor (BDNF) and neurotrophin‐3 (NT3)

Abstract: We have previously demonstrated that differentiation of hypothalamic dopaminergic (DA) neurons can be induced in culture by their pituitary intermediate lobe target cells, through both membrane and diffusible factors. We also showed that subpopulations of DA neurons from the arcuate nucleus only, not the periventricular area, can respond to the target. Here we investigated the possibility that both neuronal subsets could also respond differentially to brain-derived neurotrophic factor (BDNF) or neurotrophin-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 43 publications
(111 reference statements)
1
44
1
1
Order By: Relevance
“…4D), we concluded that they were specific NT-3 protein forms. Others have described a 35kDa NT-3 species in neuronal tissues and peripheral targets (Huff et al 1997;Loudes et al 1999;Reinshagen et al 2002), but this form was not detected in the current study using the NT-3 antibody from Santa Cruz.…”
Section: Nt-3 Protein Expression In Control Animals and Effects Of Decontrasting
confidence: 70%
“…4D), we concluded that they were specific NT-3 protein forms. Others have described a 35kDa NT-3 species in neuronal tissues and peripheral targets (Huff et al 1997;Loudes et al 1999;Reinshagen et al 2002), but this form was not detected in the current study using the NT-3 antibody from Santa Cruz.…”
Section: Nt-3 Protein Expression In Control Animals and Effects Of Decontrasting
confidence: 70%
“…The BDNF mature protein has been detected in perinatal hypothalamic tissue [10], and in arcuate and periventricular nuclei in the newborn [11]. In contrast to BDNF, NT-3 is found mostly as its precursor form in the neonatal arcuate nucleus, the 14-kD mature protein being only present in the periventricular area [11].…”
Section: Introductionmentioning
confidence: 99%
“…The BDNF mature protein has been detected in perinatal hypothalamic tissue [10], and in arcuate and periventricular nuclei in the newborn [11]. In contrast to BDNF, NT-3 is found mostly as its precursor form in the neonatal arcuate nucleus, the 14-kD mature protein being only present in the periventricular area [11]. TrkB and TrkC, the respective receptors for BDNF and NT-3, are present in most hypothalamic nuclei in the adult [12, 13, 14]; they have also been described in cultured hypothalamic neurons [15], suggesting an autocrine or a paracrine role for BDNF and NT-3 during development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In BDNFknockout mice, the density of SRIH cells is drastically reduced in hippocampus and cortex (Gro e et al 2005). In hypothalamic cultures, BDNF has been reported to have a stimulatory effect on SRIH content and mRNA expression (Rage et al 1999) and on differentiation (Loudes et al 1999). …”
Section: Introductionmentioning
confidence: 99%